-3(4-a)=-15

Simple and best practice solution for -3(4-a)=-15 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(4-a)=-15 equation:


Simplifying
-3(4 + -1a) = -15
(4 * -3 + -1a * -3) = -15
(-12 + 3a) = -15

Solving
-12 + 3a = -15

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + 3a = -15 + 12

Combine like terms: -12 + 12 = 0
0 + 3a = -15 + 12
3a = -15 + 12

Combine like terms: -15 + 12 = -3
3a = -3

Divide each side by '3'.
a = -1

Simplifying
a = -1

See similar equations:

| -2n-12=-6(2+6n) | | 96=15+9s | | 5x+6(-2+18)=157 | | 5(n+3)=3(2*n-1) | | 8y-3y=35 | | 5x+6(-2+18)=108 | | 4y=3x+C | | 63/w=9 | | 12x=5(8+2x) | | h=-2(t-1)-16t(t-1) | | XP+to=z | | 8m+10=50 | | 4(x-5)+6=2(2x-7) | | x*5+65=4*x | | 24+5h=89 | | 10x-3/12 | | X^2-9x-19/x-2 | | 2x-54=104 | | 2(x+3)+x+7=2(3x+9)+5(4-x)+3 | | 4(3x+8)=32 | | 9x+4=5x+2 | | -3(x-4)+5=-2z-2 | | 5x^4=20x^6 | | 10d+6-6d=22 | | -3(x+8)=-15 | | -5(2.5+x)=10 | | -9x^2+120x-12=0 | | -1(-3x-5)=-7 | | 0.7+y=-1.63 | | 125m-100m+43650=45225-200m | | 6/5=2/5x | | 3=-3(4x+6) |

Equations solver categories